Management of Primary Aggressive Tumors of the Knee - Martin, John R.; Auran, Richard L.; Duran, Michael D.; de Comas, Amalia M.; Jacofsky, David J. (The Journal of Knee Surgery, 2022)
Primary bone sarcomas and aggressive benign bone tumors are relatively rare. It is essential to recognize features that are concerning for these aggressive tumors based on a patient's history, physical exam, and radiographs. Physicians and other health care providers should have a high suspicion for these tumors and promptly refer these patients to orthopaedic oncologists. A multidisciplinary, team-based approach is required to obtain an accurate diagnosis and provide comprehensive care. This review discussed the appropriate work-up, biopsy principles, relevant peri-operative medical management, and surgical treatment options for patients with aggressive primary bone tumors around the knee. Primary bone sarcomas (osteosarcoma and chondrosarcoma) and aggressive benign bone tumors (giant cell tumor, chondroblastoma, and chondromyxoid fibroma) that have a predilection to the distal femur and proximal tibia are the focus of this review.
Keywords: knee joint; aggressive tumors; orthopaedic oncology; benign tumors; malignant bone tumors